A review of literature on software used in studies of life cycle - Campolina, Juliana Mendes; Sigrist, Carolina São Leandro; Moris, Virgínia Aparecida da Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The Life Cycle Assessment (LCA) is an environmental management tool used to determine the environmental impact of a product, process or service throughout its lifecycle from data collection, especially in the phase of the Life Cycle Inventory (ICV). There is a wide variety of software available in the market to assist in these studies, and considering the ease that it and provide the database for LCA, this study conducts a review of literature on the subject. By analyzing the literature, it was found that the software has several methods of analysis impacts and database processes, enabling the comparison of scenarios. The results obtained with the software are impact analysis and interpretation of the results of the system, presenting them through graphs, flowcharts and tables. The software offer database that have information on the lifecycle of products generating a reduction in the time of data collection, but it should be remembered that the database have regional character and your data should be analyzed, since the set of data from a database may not cover exactly the studied system, affecting the results.